Bactericidal effects of high intensity focused ultrasound on Bacillus Calmette–Guerin in vivo and in vitro. (1st January 2019) - Xie, Shuang; Cao, Hua; Li, Jianhu; Prasad Adhikari, Vishnu; Yang, Min; Dong, Yu; Li, Dairong; Du, Yonghong
Abstract: Purpose: The objective of this study was to investigate the bactericidal effects of high intensity focused ultrasound (HIFU) on Bacillus Calmette–Guerin (BCG, a substitute for Mycobacterium tuberculosis ) in vitro and in vivo, and to explore the underlying mechanisms. Materials and methods: HIFU, at a fixed frequency of 1 MHz, was applied to both BCG culture suspensions and subcutaneous BCG abscesses in rats. Results: HIFU irradiation significantly reduced the bacterial survival rate and caused temperature elevations both in vitro and in vivo . Furthermore, BCG suspensions irradiated for 15 s at 3185 and 6369 W/cm 2 had increased cell wall damage, which resulted in morphological changes compared to the untreated control group. Additionally, we observed histological changes in the rat subcutaneous abscesses after HIFU ablation at 6369 W/cm 2 . H&E staining of infected lesions showed coagulative necrosis with central nucleus dissolution and increased infiltration of inflammatory cells, as well as nuclear pyknosis and nuclear fragmentation in the periphery. The volumes of the subcutaneous abscesses in the HIFU-treated group were significantly lower than those in the sham-treated group. Conclusion: HIFU has the therapeutic potential to treat BCG-infected tissues in rats. We theorize that a combination of mechanical, cavitation, and thermal effects most efficiently inactivate BCG bacteria via HIFU. This study is expected to provide a bio-plausible basis for a noninvasive and effective treatment for tuberculosis.